2022
DOI: 10.3389/fneur.2022.829090
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Enriched Rehabilitation on Cognitive Function and Serum Glutamate Levels Post-stroke

Abstract: AimThis study aimed to explore the effect of enriched rehabilitation (ER) on cognitive function and serum glutamate levels in patients with stroke.MethodsForty patients diagnosed with post-stroke cognitive impairment (PSCI), according to the inclusion criteria, and undergoing inpatient rehabilitation were enrolled in the study. Patients were randomly assigned to receive 8 weeks of ER treatment (ER group; n = 20) or conventional medical treatment (CM group; n = 20). In addition, 20 age-matched healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…IDO leads to increased production of kynurenine, while kynurenine (Sapko et al, 2006) and quinolinic acid (Santamaría et al, 2001;Stone and Darlington, 2002) are involved in the induction of synaptic plasticity, and changes in these two substances' concentrations and ratios have been considered accurate indicators of PSCI (Cogo et al, 2021). Serum glutamate levels in PSCI patients further support the idea (Wang X. et al, 2022) that although glutamate is an excitatory neurotransmitter linked to cognitive function, excessive quantities might cause severe excitotoxicity that can aggravate ROS and inflammation (Liu et al, 2020b). Meng et al (2016) found that PSCI patients had a considerably lower N-acetylaspartic acid/creatine ratio in their hippocampal regions, whereas Liu et al (2015) also discovered an increase in serum creatine.…”
Section: Metabolomics In Pscimentioning
confidence: 72%
“…IDO leads to increased production of kynurenine, while kynurenine (Sapko et al, 2006) and quinolinic acid (Santamaría et al, 2001;Stone and Darlington, 2002) are involved in the induction of synaptic plasticity, and changes in these two substances' concentrations and ratios have been considered accurate indicators of PSCI (Cogo et al, 2021). Serum glutamate levels in PSCI patients further support the idea (Wang X. et al, 2022) that although glutamate is an excitatory neurotransmitter linked to cognitive function, excessive quantities might cause severe excitotoxicity that can aggravate ROS and inflammation (Liu et al, 2020b). Meng et al (2016) found that PSCI patients had a considerably lower N-acetylaspartic acid/creatine ratio in their hippocampal regions, whereas Liu et al (2015) also discovered an increase in serum creatine.…”
Section: Metabolomics In Pscimentioning
confidence: 72%
“…Furthermore, the concentration of brain-derived neurotrophic factor (BDNF) significantly increased in the treatment group, and this was significantly correlated to the functional improvement after stroke ( 10 , 14 , 15 , 28 , 34 , 36 , 41 , 47 , 48 ) ( Figure 2 ; Table 1 ). Compared to the control group, the low-quality evidence in the treatment group revealed that the concentration of serum noradrenaline (NE) increased ( 27 , 28 , 36 ), while the concentrations of serum endothelin (ET) ( 39 , 44 , 46 ) and glutamate ( 36 , 40 , 42 ) decreased, and these were significantly associated with the functional improvement after stroke ( Supplementary Figures S2–S4 ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%